Evaluasi Program Pendidikan Keluarga di Instalasi Kesehatan Jiwa Masyarakat Rumah Sakit Jiwa Grhasia Daerah Istimewa Yogyakarta - Cicilia Nindi Arsita (Universitas Ahmad Dahlan, 2021)
The Family Education Program is a program that aims to increase the capacity of caregivers in mentoring ODGJs. Program evaluation is needed in order to know how the condition of the evaluation object is in the design, implementation and results. The purpose of this study is to evaluate the family education program in the Community Mental Health Installation at the Grhasia Mental Hospital Special Region of Yogyakarta. This type of research is qualitative with a case study approach. The sampling technique in this study was divided into two, namely the subject of implementing the program using total sampling and the subject of the program's target using purposive sampling. The data in this study were obtained from in-depth interviews. In this variable it is good, the Family Education program does not have a certain Standars Prosedures but has a Terms of Reference for Activities that are compiled in accordance with Permenkes RI No. 44/2018. In quantity, it is sufficient by dividing the jobdesk according to their respective abilities. The budget spent is sufficient and allocated for program needs such as: stationery, modules, participant transport, snacks / consumption and others. The facilities used in the Family Education program are accordance with the Republic of Indonesia Minister of Health Regulation No. 44/2018. Program planning is carried out at the end of each period involving all of the Keswamas human resouces. Program supervision is carried out by the Technical Implementation Officer appointed by the Hospital. Supervision is also carried out during the learning process, to see the abilities of the participants. Program achievement can be seen from the pre-post test results, attendance of participants, and participant testimony. The pre-post test results show that the post test results are greater. The attendance of participants in every meeting is still inconsistent in the sense that there are still participants who are still absent in every meeting. Testimony of participants said that the Family Education program is very important and has a positive impact not only for participants but also for patients and other families. Overall the Family Education program is good. This can be seen from the human resources, adequate budget and facilities, planning in accordance with applicable policies, and high program achievement seen from the pre-post results, attendance of participants and testimonials.